Technology for modelling a sociological study of social conflicts in the sphere of sports - Peredelskiy, A.A.; Donskikh, K.Yu.; Arzamastseva, N.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is the development of a technology for modelling a sociological study of social conflicts in the sphere of sports, providing for certain variants of their prevention and resolution. Methods and structure of the study. This work represents a descriptive sociological study, built and organised on the basis of the consistent use of the sociological methods of document analysis and participant observation, and the general-scientific operations of typologisation and modelling. Results and conclusions. The results of the conducted study prove the possibility of constructing a relatively universal model of a sociological study of social conflicts in the sphere of sports. The indicated model includes the logic of constructing a typical structural-content map and a typical scientific thesaurus filling the sociological toolkit. However, the profile-applied application of this technology for modelling a thematic sociological study is necessarily connected with the knowledge of various levels and fragments of management and organisation in the sphere of sports, sports activity, sports management, and sports education, without which the indicated sociological model is deprived of a practical foundation and turns into a pure abstraction. Accordingly, each particular profile-applied model of the technology of a sociological study of a social crisis in the sphere of sports will necessarily require the development of a particular thesaurus as well, adapting the sociological toolkit to the specifics of the level and fragment of socio-crisis counteraction under consideration.